Effects of acculturative stress on PTSD, depressive, and anxiety symptoms among refugees resettled in Australia and Austria. Issue 1 (1st December 2016) - Kartal, Dzenana; Kiropoulos, Litza
Abstract : Background: Research indicates that exposure to war-related traumatic events impacts on the mental health of refugees and leads to higher rates of posttraumatic stress disorder (PTSD), depression, and anxiety symptoms. Furthermore, stress associated with the migration process has also been shown to impact negatively on refugees' mental health, but the extent of these experiences is highly debatable as the relationships between traumatic events, migration, and mental health outcomes are complex and poorly understood. Objective: This study aimed to examine the influence of trauma-related and post-migratory factors on symptoms of PTSD, depression, and anxiety in two samples of Bosnian refugees that have resettled in two different host nations—Austria and Australia. Method: Using multiple recruitment methods, 138 participants were recruited to complete self-report measures assessing acculturative stress, PTSD, depressive, and anxiety symptoms. Results: Hierarchical regressions indicated that after controlling for age, sex, and exposure to traumatic events, acculturative stress associated with post-migratory experiences predicted severity of PTSD and anxiety symptoms, while depressive symptoms were only predicted by exposure to traumatic events. This model, however, was only significant for Bosnian refugees resettled in Austria, as PTSD, depressive, and anxiety symptoms were only predicted by traumatic exposure in the Bosnian refugees resettled in Australia. Conclusion: These findings point toward the importance of assessing both psychological and social stressors when assessing mental health of refugees. Furthermore, these results draw attention to the influence of the host society on post-migratory adaptation and mental health of refugees. Further research is needed to replicate these findings among other refugee samples in other host nations.